The Effect of Using the Instagram Application on the Learning Outcomes of Aqidah Akhlak Subjects - Muhammad Faisal Arsyad; Imam Suhadi (PALAPA, 2025)
This study explores the under-researched role of social media, specifically Instagram in the learning of Aqidah Akhlak, a core component of Islamic education, and its impact on student learning outcomes and character development. The research focuses on 8th-grade students at Al Abidin Bilingual Boarding School Surakarta during the 2024/2025 academic year. Employing a quantitative correlational survey design, the study involved 60 students selected through purposive sampling. Data were collected using a structured questionnaire on Instagram usage and documented learning outcomes, then analyzed using simple linear regression with SPSS version 25. The results reveal a very strong positive correlation between Instagram use and Aqidah Akhlak learning outcomes (r = 0.901, p < 0.01), suggesting that Instagram, when used constructively, can serve as an effective learning medium. This aligns with constructivist, connectivist, and social learning theories that highlight the value of interactive digital experiences and networked learning environments. However, the study also cautions against excessive use, which may lead to distraction. Theoretical implications include the expansion of literature on social media-based Islamic education, while practical implications point to the need for schools and educators to incorporate Islamic digital literacy into curriculum design. The study also opens avenues for further research using experimental or mixed-method approaches to investigate motivational factors and the internalization of moral values through social media platforms.